Inspiratory muscle training is ineffective in mechanically ventilated critically ill patients (Clinics, 2005)
PURPOSE: Invasive mechanical ventilation is associated with complications, and its abbreviation is desirable. The imbalance between increased workload, decreased inspiratory muscle strength and endurance is an important determinant of ventilator dependence. Low endurance may be present due to respiratory muscle atrophy, critical illness, or steroid use. Specific inspiratory muscle training may increase or preserve endurance. The objective of the study was to test the hypothesis that inspiratory muscle training from the beginning of mechanical ventilation would abbreviate the weaning duration and decrease reintubation rate. As a secondary objective, we described the evolution of inspiratory muscle strength with and without inspiratory muscle training. METHODS: Prospective, randomized clinical trial in an adult clinical-surgical intensive care unit. Twelve patients trained the inspiratory muscles twice a day, and 13 patients did not (control). Training was performed adjusting the sensitivity of the ventilator based on the maximal inspiratory pressure. Patients underwent daily surveillance of the maximal inspiratory pressure. RESULTS: The weaning duration (31 ± 22 hr, control and 23 ± 11 hr, training group; P = .24) and reintubation rate (5 control and 3 training group; P = .39) were not statistically different. The maximal inspiratory pressure of the control group showed a trend toward a modest increase. In contrast, the training group showed a small decrease (P = .34). CONCLUSIONS: In acute critically ill patients, inspiratory muscle training from the beginning of mechanical ventilation neither abbreviated the weaning duration, nor decreased the reintubation rate. Inspiratory muscle strength tended to stay constant, along the mechanical ventilation, with or without this specific inspiratory muscle training.